Pengaruh Profitabilitas, Risiko Perusahaan, dan Ukuran Perusahaan Terhadap Audit Fee - Rahman, Muhammad Hafizur; Musyaffi, Ayatulloh Michael; Nindito, Marsellisa (LPPM Universitas Negeri Jakarta, 2024)
This study aims to explore the relationships that exist between audit fees and corporate risk, profitability, and firm size. The dependent variable is the audit fee as measured by its natural logarithm. Then, for independent variables, business size is determined by taking the natural logarithm of total assets, firm risk is computed by dividing total liabilities by total equity, and profitability is evaluated by dividing net profit by sales, or net profit margin. This analysis makes use of secondary data from a population of manufacturing sector enterprises that registered on the IDX between 2020 and 2022. The sample was selected through purposeful sampling, which produced forty-three enterprises. Eviews 13 was used in the panel data regression analysis method used in this investigation. According to this study, profitability has a detrimental effect on audit fees. Consequently, company risk has no beneficial effect on audit fees. Then, audit fees are positively impacted by the company's size.